Erythrocyte type 1 equilibrative nucleoside transporter expression in sickle cell disease and sickle cell trait. (4th December 2022) - Koehl, Bérengère; Claude, Livia; Reminy, Karen; Tarer, Vanessa; Baccini, Véronique; Romana, Marc; Colin‐Aronovicz, Yves; Damaraju, Vijaya L.; Sawyer, Michael; Peyrard, Thierry; Etienne‐Julan, Maryse; Le Van Kim, Caroline; et al.
Summary: Hypoxia‐mediated red blood cell (RBC) sickling is central to the pathophysiology of sickle cell disease (SCD). The signalling nucleoside adenosine is thought to play a significant role in this process. This study investigated expression of the erythrocyte type 1 equilibrative nucleoside transporter (ENT1), a key regulator of plasma adenosine, in adult patients with SCD and carriers of sickle cell trait (SCT). Relative quantitative expression analysis of erythrocyte ENT1 was carried out by Western blot and flow cytometry. Patients with SCD with steady state conditions, either with SS or SC genotype, untreated or under hydroxycarbamide (HC) treatment, exhibited a relatively high variability of erythrocyte ENT1, but with levels not significantly different from normal controls. Most strikingly, expression of erythrocyte ENT1 was found to be significantly decreased in patients with SCD undergoing painful vaso‐occlusive episode and, unexpectedly, also in healthy SCT carriers. Promoting hypoxia‐induced adenosine signalling, the reduced expression of erythrocyte ENT1 might contribute to the pathophysiology of SCD and to the susceptibility of SCT individuals to altitude hypoxia or exercise to exhaustion.